International Mergers and Acquisitions Laws, the Market for Corporate Control, and Accounting Conservatism - KHURANA, INDER K.; WANG, WEI (Journal of Accounting Research, 2019)
ABSTRACT Exploiting the staggered enactment of country‐level mergers and acquisitions (M&A) law as an exogenous increase in corporate takeover threat, this paper examines how a disciplinary market for corporate control affects accounting conservatism. Following M&A law adoption, we find increased accounting conservatism, with more pronounced effects in countries with weak shareholder protection and in those experiencing larger growth in takeover activity. Further analysis reveals that elevated takeover threats increase conservatism through changes in capital structure and investment decisions as well as improvements in board monitoring. Our findings highlight the importance of the market for corporate control in shaping financial‐reporting outcome.